New mammary epithelial and fibroblastic cell clones in coculture form structures competent to differentiate functionally (The Rockefeller University Press, 1989)
We have established and characterized a spontaneously immortalized, nontumorigenic mouse mammary cell line, designated IM-2. IM-2 cells synthesize large amounts of the milk protein beta-casein upon addition of lactogenic hormones. The induction of beta-casein occurs rapidly and does not require any exogenous extracellular matrix components. The IM- 2 cell line is morphologically heterogeneous and could be separated into cell clones with epithelial and fibroblastic characteristics. In monoculture, none of the epithelial clones could be induced to synthesize caseins. Coculture of epithelial and fibroblastic clones, however, rendered the epithelial cells competent to differentiate functionally; the addition of lactogenic hormones to these cocultures resulted in the synthesis of beta-casein in amounts comparable to that seen with the original IM-2 line. Using this unique cell system, we have investigated the interrelationships between different steps in differentiation leading to hormone-induced casein production. Independent of hormones, epithelial-fibroblastic cell contacts led to the formation of characteristic structures showing the deposition of laminin. We found that the epithelial cells located in these structures also exhibited significantly increased levels of cytokeratin intermediate filament polypeptides. Double immunofluorescence revealed that the cells inducible by hormones to synthesize casein, colocalized exactly with the areas of laminin deposition and with the cells showing greatly intensified cytokeratin expression. These results suggest that hormone-independent differentiation events take place in response to intercellular epithelial-mesenchymal contacts. These events in turn bring about a state of competence for functional differentiation after lactogenic hormonal stimulation.